Structure-activity relationship of the pro- and anticoagulant effects of Fucus vesiculosus fucoidan - Zhang, Z; Till, S; Jiang, C; Knappe, S; Reutterer, S; Scheiflinger, F; Szabo, C M; Dockal, M (Thrombosis and haemostasis, 2014)
Fucoidan is a highly complex sulfated polysaccharide commonly extracted from brown seaweed. In addition to their many biological activities, fucoidans have recently been demonstrated to inhibit or increase coagulation at different concentration ranges. Their structural features, i.e. molecular weight (Mw), Mw distribution, degree of sulfation, monosaccharide composition, and different linkages, are known to affect these activities. Therefore, structure-activity relationship (SAR) analysis of fucoidan is crucial for its potential use as a procoagulant. In this study, Fucus vesiculosus (F.v.) fucoidan was fractionated by charge and size as well as over- and desulfated to different degrees to yield preparations with various structural properties. The fractions' pro- and anticoagulant activities were assessed by calibrated automated thrombography (CAT) and activated partial thromboplastin time(aPTT) assays. Binding to and inhibition of the anticoagulant protein tissue factor pathway inhibitor (TFPI) and the ability to activate coagulation via the contact pathway were also investigated. This paper discusses the impact of charge density, size, and sugar composition on fucoidan's pro- and anticoagulant activities. Fucoidan requires a minimal charge density of 0.5 sulfates per sugar unit and a size of 70 sugar units to demonstrate desired procoagulant activities for improvement of haemostasis in factor VIII/factor IX-deficient plasma.